Migration and Religion Christian Transatlantic Missions, Islamic Migration to Germany. - Becker-Cantarino, Barbara (Amsterdam : Editions Rodopi, 2012)
This volume looks at how religious identity and symbolic ethnicity influence migration. Religion - Christianity - was an important factor in European transatlantic migrations; religion - Islam - is a major issue in the immigration debate in "post-secular" Germany (and Europe) today. Essays focus on German missionaries and their efforts in the eighteenth century to establish new communal forms of living with Native Americans as religious encounters. In a comparative fashion, Islamic transnational migration into Germany in the twenty-first century is explored in a second group of essays that loo
Description based upon print version of record.
Keywords: Christianity and other religions; Muslims -- Non-Muslim countries; Muslims -- Germany; Emigration and immigration -- Religious aspects; Christianity and other religions; Emigration and immigration -- Religious aspects; Muslims -- Germany; Muslims -- Non-Muslim countries; RELIGION / Christian Life / General; Electronic books